Effectiveness of a Structured Teaching Program on Attitudes toward Air Pollution among Shopkeepers - Rohan Janardan Kamble; Richa Jadhav; Shivagouda Patil, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Air pollution is a major environmental health issue, contaminating the atmosphere with harmful pollutants that adversely affect human health, ecosystems, and materials. In India, over 76% of the population is exposed to ambient particulate matter exceeding national guidelines, contributing to millions of disability-adjusted life years (DALYs). Shopkeepers in urban areas like Kolhapur face heightened exposure due to traffic and industrial activities, yet their attitudes toward air pollution remain understudied. The present study aimed to evaluate the effectiveness of a structured teaching programme (STP) on attitudes regarding air pollution among shopkeepers in selected areas of Kolhapur, Maharashtra, India. Objectives: 1. To assess the attitude scores regarding air pollution among shopkeepers. 2. To evaluate the effectiveness of STP on attitudes toward air pollution among shopkeepers. 3. To find the association between mean pre-test attitude scores and selected socio-demographic variables. Methods: A quantitative evaluative approach was used, with a pre-experimental one-group pre-test-post-test design. A sample of 60 shopkeepers was selected using non-probability purposive sampling technique. Attitudes were measured using a structured 5-point Likert scale (28 items; Cronbach's alpha = 0.75). Data were collected via pre-test on September 10, 2024, followed by STP implementation, and post-test on September 16, 2024. Result: The majority of shopkeepers (65%) had negative attitudes in the pre-test, with a mean score of 85.5 ± 7.54. Post-test showed 80% positive attitudes, with a mean score of 110.7 ± 5.27. Paired t-test indicated significant improvement (t = 20.65, p = 0.01). No significant associations were found between pre-test scores and socio-demographic variables (p > 0.05). Interpretation and conclusion: The study concludes that shopkeepers in Kolhapur exhibited deficient attitudes toward air pollution pre-intervention, but the STP significantly improved these attitudes. There is a need for healthcare professionals, particularly nurses, to implement educational programs addressing air pollution awareness among vulnerable occupational groups. The findings have implications for nursing practice, education, administration, and research. Recommendations for future studies and interventions to enhance community health are also provided.